Marine debris monitoring & assessment using standing-stock survey at selected beaches along Pahang coastline - Azman, Muhammad Afiq; Ramli, Muhammad Zahir; Che Othman, Siti Fairuz; Shafiee, Saiful 'Arifin (2020)
Marine debris accumulation governed by three factors; The emission rate of plastics into oceans, the amount of plastics already present in oceans, the degradation rate of plastics. • Such efforts of Malaysia on reducing marine debris are Roadmap Towards Zero Single-use Plastics 2018-2030 and joining The Coordination Body of the Seas of East Asia (COBSEA) to deliver target SDG 14. • This study was one of the collaborative subproject to contribute databases initiated by UN Environment Program (UNEP) and Marine Debris Monitoring and Assessment Program (MDMAP) by NOAA